Affect is not innocent: How affect can evolve into an ideological space. - Van Tourhout, Benjamin (Journal of European Popular Culture, 2020)
While being affected, as the processural embodiment of emotions, is often seen with positive bias and as a literary or aesthetic quality, I will argue that affectivity is not restricted to emotive or aesthetical happenings, but that it opens ways to share ideologies through narratives. Due to affects that audiences experience, they can evolve into a state of being morally off-guard due to the profound emotive response to certain dramatic elements. Heroic elements in narratives seem to amplify such uncritical acceptance of both behaviour and ideologies. They allow audiences to embrace ideas they might otherwise reject because of their allegiance to heroized figures. The article elaborates on this specific ideological element of spectatorship and discusses it within the field of performing arts by making reference to the work of, among others, The Panic Movement, Jerzy Grotowski and Romeo Castellucci. I will analyse the strategies employed in performing arts to create affective experiences, such as mirror neurons, transparency, shock effects or alienating effects. The article combines insights from the research field of spectatorship and morality, as affect allows audiences to side with ideologies they would normally oppose. I argue that affect is not only a highway to the heart of audiences but can simultaneously be a silencer for the moral mind.